BIChromET: A Chromogenic Culture Medium for Detection of Piperacillin/Tazobactam and Cefepime Resistance in Pseudomonas aeruginosa - José Manuel Ortiz de la Rosa; Ángel Rodríguez-Villodres; Guillermo Martín-Gutiérrez; Carmen Cintora Mairal; José Luis García Escobar; Lydia Gálvez-Benítez; José Miguel Cisneros; José Antonio Lepe (MDPI AG, 2023)
Objectives: The BIChromET selective medium for detecting piperacillin-tazobactam (TZP) and cefepime (FEP) resistant Pseudomonas aeruginosa was developed. Methods: The performance of this medium was first evaluated using a collection of 100 P. aeruginosa clinical strains (70 TZP-susceptible, 30 TZP-resistant, 58 FEP-susceptible, and 42 FEP-resistant). Then, we performed clinical validation by testing 173 respiratory clinical samples. Results: The BIChromET medium showed excellent sensitivity (TZP (avg. 96.7%); FEP (avg. 92.7%)) and specificity (TZP (avg. 98.9%); FEP (avg. 98%)) in distinguishing the detection limit ranging from 104 to 108 CFU/mL. Then, testing the bronchoalveolar lavage (BAL) and tracheobronchial aspirate (TBA) clinical specimens (N = 173) revealed the excellent performance of the medium with P. aeruginosa, showing 100% and 92.6% of categorical agreements with the results obtained via the broth microdilution methods (BMD) for TZP and FEP, respectively. Conclusion: This medium allows for easy and accurate detection of TZP/FEP-resistant isolates regardless of their resistance mechanisms.